AGAMA DAN PENCERAHAN BUDAYA : INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA BUDAYA MASYARAKAT INDONESIA - Sazali Sazali (Populis : Jurnal Sosial dan Humaniora, 2016)
Islam in the realm of culture has shown its unique dynamics. Besides being a cultural force, Islam, for example, has emerged as a resistance movement faced colonialism. In Indonesia, although Islam has become the "face" of the nation, its history has spawned several interpretations of thought which is viewed differently. This interpretation by itself has shown that the treasures of Islamic culture is not limited to understandings rigid theological and doctrinal alone. On the side of the paradox, Islam as a religion is a cultural force has caused the turmoil that is often unfairly accused. Adults have often campaigned that Islam as a religion of civilization has become a "threat" to the contemporary western world. As a cultural reality, Islam has always claimed to be a universal dimension and perform a variety of adaptations. In fact, in the development of its history, Islam often do contiguity are open to various local cultural areas targeted syiarnya. Islam also widened tolerant of local cultures. In a local view, we are certainly not too surprised, how Islam as a theology, for example, capable of combining with Javanese and Hindu syncretism understood that for centuries has been influenced each other. Islam as a culture has given a touch of "flexible and intimate" against the values of the local culture. By itself, this show Islam as a cultural reality has to ask himself. As far as can be mapped "cultural blindness" would occur in the region basically, that is the psychological dimensions-mental, so actuality cultured most Muslims are actually many detrimental to the development of Islamic culture. If Islam truly a religion that was revealed to the benefit of all the Worlds and its contents, it's time boundaries of formal-structural rigid avoided. Thus, it should be removed impression that when the advance of civilization and culture, it is precisely the religion (Islam) blocking it. The task of religion (Islam) should lead to progress and as he guided her.  Keywords : Islamic doctrine, the Indonesian history, “modernity” of values, inclusivness